Reduction of Microbial Content (Escherichia coli) in Well Water Using Various Processes: Microfiltration Membranes, Aeration and Bentonite Adsorption - Lala, Andi; Marlina, Marlina; Yusuf, Muhammad; Rivansyah Suhendra; Maulydia, Nur Balqis; Muslem, Muslem (Heca Sentra Analitika, 2023)
Water is a basic need for living things. This research aims to know the reduction of microbe content (Escherichia coli) in well water by using microfiltration membrane, adsorption using bentonite and aeration. The capability of those three methods in reducing E. coli was examined on the variety of time contact: 30, 60, 90, 120,180 and 300 minutes. The result of the research shows that using those methods has shown that the optimum percentage of E. coli reduction by using microfiltration membrane with 23 Most Probable Number (MPN)/100 mL of E. coli initial concentration in well water and became 0 MPN/100 mL by 100 % of E. coli reduction. Adsorption using bentonite resulted in a 78% reduction in E. coli and reduction by using aeration, the reduction of E. coli by 21%. This study shows that microfiltration has the best ability compared to other methods.